An analysis study on the students’ ability in using past tense - Muhamad Sarifuddin (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
This is an analysis study that focused on identifying the students’ ability in using simple past tense. this study is conducted on students of Al-Buhary Islamic Boarding school Praya central Lombok West Nusa Tenggara in academic year 2025-2026. The boarding school is actually occupied by 184 students in which they are on the junior high school and senior high school level. However, samples were used as the researcher could not cope with the whole population. The samples consisted of 50 students that taken from the students of junior high school level. The students’ ability in this case is identified on the students’ accuracy and fallacy one in using English simple past tense. The fallacy or inaccuracy is the main point of this investigations. The result of farther analysis shows that the students seemingly have problems in three categories, they are omission, addition, and malformation of English simple past tense. Thus, the students were often found to make fallacy in using those patterns high. The average number of in accuracy or fallacy made of all the students was 45%. From the percentage, it can be concluded that the students’ mastery in using English simple past tense was fair category. It is hoped that the finding of the present study will be useful for the teaching of English, especially the teaching of English simple past tense.